Interactive technologies as a means of pedagogical training for future physical education teachers - Voishcheva, E.L.; Zaharova, M.A.; Karpacheva, I.A.; I.B. , Larina (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop professional competencies in future physical education teachers through digital educational content and interactive technologies. Methods and structure of the study. The databases ‘Practical Training in Pedagogy: Didactics’ and ‘Practical Training in Pedagogy: Theory and Methods of Education’ served as educational content for the development of practice-oriented case studies. Immersion in the interactive environment was achieved through group defence of the completed case studies. The research base was the I.A. Bunin Yelets State University (Lipetsk Oblast). Results and conclusions. Diagnostic work was carried out in the discipline of ‘Pedagogy.’ According to the results, the majority (44%) of students are at an average level of professional competence. During interactive problem-solving and group case studies, future physical education teachers master the solution of pedagogical-type tasks in their professional activities.